2009
DOI: 10.1097/brs.0b013e31819c9d5b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Analysis on Lumbar Disc Herniation Using Surgical Specimens

Abstract: The inflammatory response that occurs around hernia tissue in the epidural space is believed to play an important role in herniated disc resorption, although it may also have a harmful effect on the adjacent nerve root. Therefore, control of the inflammatory reaction is an important challenge when treating patients with disc herniation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 34 publications
2
63
0
Order By: Relevance
“…In the current study, IVDs from patients with NCDH had significantly more neovascularization and granulation tissue than patients with CDH. This is consistent with results from previous studies (37,47), which showed that annulus fibrosus disruption could induce changes in the microenvironment surrounding herniated disc tissues. The present study evaluated the differences in neovascularization between the CDH and NCDH groups; however, no post-treatment follow-up evaluations were performed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the current study, IVDs from patients with NCDH had significantly more neovascularization and granulation tissue than patients with CDH. This is consistent with results from previous studies (37,47), which showed that annulus fibrosus disruption could induce changes in the microenvironment surrounding herniated disc tissues. The present study evaluated the differences in neovascularization between the CDH and NCDH groups; however, no post-treatment follow-up evaluations were performed.…”
Section: Discussionsupporting
confidence: 82%
“…Paraffin sections (5-µm-thick) were cut and stained with hematoxylin and eosin and toluidine blue. Surgical specimens were qualitatively graded according to whether or not inflammatory changes existed in the herniation (47) (Fig. 1) and hypertrophic chondrocytes were present in the specimens (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…An increase in expression of some cytokines and MMPs in herniated IVD may occur when molecules seen as 'non-self' by immune cells become exposed. This may also be linked to the phenomenon of spontaneous regression or disappearance of extruded IVD fragments, which has been attributed to matrix degradation and phagocytosis by recruited/infiltrated macrophages [102][103][104][105][106]. In cases with transligamentous extrusion, which can occur when the NP is potentially more exposed to immune cells, regression occurs [107].…”
Section: Mmp19mentioning
confidence: 99%
“…The spontaneous resorption of prolapsed lumbar IVD tissue has frequently been observed [23-25] although the exact mechanisms by which this occur are not yet fully understood. Inflammatory and autoimmune responses provoked in the innate and adaptive immune systems on detection of displaced tissue likely play a role, with infiltrating monocytes [26], macrophages [26-29], T and B lymphocytes [27,28] and fibroblasts [29] reported in prolapsed NP tissue.…”
Section: Introductionmentioning
confidence: 99%